Analisis Kesalahan Morfologis pada Platform X - Veny Fitriana Rahman; Laili Amalia (STKIP Subang, 2026)
ABSTRACT This study aims to describe the forms of morphological errors found in users’ posts on Platform X (formerly Twitter). Morphological language errors have become a significant phenomenon as informal digital communication continues to develop, where the speed of message delivery is often prioritized over adherence to standard grammatical rules. This research employed a qualitative descriptive approach. The data sources consisted of posts, captions, comments, and replies from Platform X users that contained indications of grammatical deviations at the morphological level. Data were collected through observation, reading, and documentation techniques (screenshots), followed by data reduction, data presentation, and conclusion drawing. The findings revealed three main types of morphological errors: affixation errors, compounding errors, and reduplication errors. Affixation errors were the most dominant type, characterized by the omission of prefixes, the inappropriate selection of affixes, and the incorrect use of allomorphs. These findings indicate that character limitations and the spontaneous nature of digital communication contribute to the high frequency of non-standard language use in digital spaces. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan bentuk-bentuk kesalahan morfologis yang terdapat pada unggahan pengguna di platform X (sebelumnya Twitter). Kesalahan berbahasa pada tataran morfologi menjadi fenomena yang signifikan seiring berkembangnya interaksi digital informal yang mengutamakan kecepatan penyampaian pesan dibanding ketepatan kaidah tata bahasa. Pendekatan yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Sumber data berupa teks unggahan (caption), komentar, dan balasan dari akun resmi pengguna platform X yang mengandung indikasi kesalahan morfologis. Teknik pengumpulan data menggunakan metode simak dan catat, yang dilanjutkan dengan reduksi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan adanya tiga bentuk utama kesalahan morfologis, yaitu kesalahan afiksasi, kesalahan komposisi (pemajemukan), dan kesalahan reduplikasi (pengulangan kata). Kesalahan afiksasi merupakan jenis kesalahan yang paling dominan, yang ditandai dengan pelesapan prefiks, ketidaktepatan pemilihan bentuk afiks, serta penggunaan alomorf yang keliru. Fenomena ini mengindikasikan bahwa keterbatasan karakter dan karakteristik komunikasi digital yang spontan memicu tingginya intensitas penggunaan ragam nonbaku di ruang digital.